HIV replication and latency in monocytes and macrophages. (January 2021) - Veenhuis, Rebecca T.; Abreu, Celina M.; Shirk, Erin N.; Gama, Lucio; Clements, Janice E.
Abstract: The relevance of monocyte and macrophage reservoirs in virally suppressed people with HIV (vsPWH) has previously been debatable. Macrophages were assumed to have a moderate life span and lack self-renewing potential. However, recent studies have challenged this dogma and now suggest an important role of these cell as long-lived HIV reservoirs. Lentiviruses have a long-documented association with macrophages and abundant evidence exists that macrophages are important target cells for HIV in vivo. A critical understanding of HIV infection, replication, and latency in macrophages is needed in order to determine the appropriate method of measuring and eliminating this cellular reservoir. This review provides a brief discussion of the biology and acute and chronic infection of monocytes and macrophages, with a more substantial focus on replication, latency and measurement of the reservoir in cells of myeloid origin.